The Mirror and the Double: Analysis of two Mirror texts by Vittorio Sereni on a petrarchan Track (Il sabato tedesco e Un posto di vacanza) (inOpera Esercizi di lettura su testi contemporanei, 2025)
In Sereni’s poetic and prose corpus, the topos of the mirror is recurrent. In light of this constant theme, literature is conceived as a form of mirroring of interior and exterior reality. The idea of ​​art as a specular/speculative process, however, goes beyond the notion of pure mimesis of the self and the world, since the image that returns to the subject from a reflecting surface is never fixed but changeable and, at most, elusive. The use of this emblem is charged with a strong semantic significance in the production between the end of the Seventies and the beginning of the Eighties. In this essay, the detailed investigation focuses precisely on two key texts from Sereni’s late period: Il sabato tedesco and Un posto di vacanza.
Keywords: Mirror; Time; Self-citation; Intertextuality; Narrative Literature; Petrarchism; Doubling